Monitoring the Biophysical Profile of the Mangrove Ecosystem in Sedari Village, Cibuaya District, Karawang Regency, West Java - Endy Handayani; Dwi Rosalina; Riza Rizkiah; R. Moh. Ismail; Suko Wardono; Muhammad Yusuf; Budi Sulistiyo (JURNAL ENGGANO, 2026)
Monitoring the biophysical profile of the mangrove ecosystem is an activity aimed at collecting data related to the physical, biological, and chemical conditions of the mangrove ecosystem. This monitoring activity was conducted in Sedari Village, Cibuaya District, Karawang Regency, which has coastal topography, from September 9 to November 18, 2024. The objective of this study is to analyze the physical and biological characteristics of the mangrove ecosystem in Sedari Village and to evaluate the water quality in the surrounding area. Data collection was carried out through a combination of field survey techniques, direct measurements, laboratory analyses, and the use of photogrammetry techniques with drone platforms.  The results of the study on physical parameters showed that water temperature ranged between 30–34.1°C, pH values ranged from 5 to 6, salinity was 30 ppt, and the tidal range in the waters of Sedari reached a maximum high tide of 0.6 meters.  The analysis of mangrove density along the coastline of Sedari Village showed a value of 0.33 trees/m², equivalent to 3,300 trees/hectare.  Water quality data revealed the following results: the Total Dissolved Solids (TDS) values at the three observation stations exceeded 30,000 mg/L, with the highest BOD value recorded at Station 1 reaching 211 mg/L, and COD at 704 mg/L. The concentrations of nitrate and phosphate were very low, at 0.01 mg/L and 0.015 mg/L respectively.  Overall, these conditions reflect significant environmental stress on the mangroves, primarily due to organic and chemical pollution. Keywords: Monitoring, Biophysical, Water quality, Sedari mangroves